The Cruise/Vessel Characteristics Of Inland Waterways - Tjahjono, A Agus (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
Inland water shipping has not been used maximally, its utilization is still very minimal. Though the opportunities for good use for the purpose of transportation of goods, passengers, tourism are still very broad, very cheap for the transportation of goods in large quantities such as those which began to be developed on the islands of Kalimantan and Sumatra for transportation of mining products and agricultural products2 . Sailing through rivers and lakes is one form of transportation system that is used to transport goods and passengers through inland waters. This transportation system is a transportation that has developed since prehistory which then developed into the main transportation system in certain regions even in more developed areas such as the European transportation system. In river shipping various kinds of goods are transported from the hinterland to the port. Conversely, through the river also goods from the port are distributed to areas in the interior. The same thing happens in lakes, various kinds of goods are transported to and from cities on the other side of the lake. Sailing of rivers and lakes has an important role3 in transporting trade goods. Agricultural products, livestock / fisheries and forest products are one of the main commodities transported via river shipping. In addition, mining and handicraft products of the population.